Inoculation with arbuscular micorrizhal fungi and organic compost from cocoa shell positively influence the growth and mineral nutrition of soursop plants (Annona muricata l.) - Gedeon Almeida Gomes Júnior; Rafaela Alves Pereira; George Andrade Sodré; Célio Kersul do Sacramneto; Eduardo Gross (Revista Brasileira de Fruticultura, 2018)
Abstract The aim of this study was to evaluate the effect of arbuscular mycorrhizal fungi inoculation (AMF - Acaulospora scrobiculata, Acaulospora colombiana and the mixture of these inocula) and doses of organic compost obtained from cocoa shell (0, 5, 10, 20 and 30 g dm-3) on “Morada” soursop seedlings. The experimental design was a randomized block with 4 blocks in a 5 x 4 factorial scheme (AMF x organic compost). After 120 days of growth, it was observed that AMF inoculation increased height, stem diameter and shoot, root and total dry biomass. Organic compost stimulated mycorrhizal colonization and the number of spores with the addition up to 10 g dm-3. Mycorrhizal inoculation promoted increases of P content in soursop leaves. Control plants did not show adequate response to doses of the organic compost applied and it was concluded that AMF inoculation combined with organic compost increased the growth and nutrition of soursop plants.